High Quality Paper award IEEE PES 2019 PowerTech - Aristidou, Petros (My University, 2026)
High-Quality Paper award for paper ’Interval-Based Adaptive Inertia and Damping Control of a Virtual Synchronous Machine’, IEEE PES 2019 PowerTech, Milan (honorary diploma) Role: co-author
Keywords: Sciences